Poor sleep quality and associated factors among HIV-positive and negative postpartum women in Addis Ababa, Ethiopia: a comparative cross-sectional study - Mihertabe, Milen; Geremew, Alehegn Bishaw; Fentie, Elsa Awoke; Rtbey, Gidey (Frontiers in Psychiatry, 2025)
BackgroundPoor sleep quality is common during the postpartum period due to nighttime feeding and frequent nocturnal awakenings of infants. In addition, the condition may worsen among postpartum women living with human immunodeficiency virus (HIV), affecting their capacity to care for their child. Therefore, this study will provide baseline information by assessing the burden of poor sleep quality and associated factors among HIV-positive and negative postpartum women in Addis Ababa, Ethiopia.ObjectiveThe aim of this study was to assess poor sleep quality and its associated factors among HIV-positive and negative postpartum women in Addis Ababa, Ethiopia in 2023.MethodsA comparative cross-sectional study was conducted from 20 March to 20 May 2023, and a systematic random sampling technique was employed to obtain a total of 535 study subjects. An interviewer-administered questionnaire and chart review were used to collect the data. The Pittsburgh Sleep Quality Index was used to assess the outcome variable with a cutoff point ≥5. Binary logistic regression was employed to check the association of each independent variable with the outcome variable. Variables having a p-value of less than 0.05 in multivariable analysis were considered statistically significant and an adjusted odds ratio with a 95% confidence interval (CI) was computed.ResultsIn this study, the overall prevalence of poor sleep quality among postpartum women was 56.3% [95% CI (51.9, 60.6)]. Poor sleep quality prevalence among HIV-positive and -negative women was 80% and 50.5%, respectively. Being HIV-positive [AOR = 2.38, 95% CI (1.31, 4.32)], being divorced [AOR = 4.5, 95% CI (1.55, 13)], and having a family history of mental illness [AOR = 1.89, 95% CI (1.16, 3.1)], depression [AOR = 1.93 (1.11, 3.3)], and anxiety [AOR = 2.76, 95% CI (1.8, 4.2)] among postpartum women and poor social support [AOR = 6, 95% CI (1.63, 22.4)] among HIV-positive women were significantly associated with poor sleep quality.Conclusion and recommendationThis study revealed that the prevalence of poor sleep quality was higher among HIV-positive postpartum women compared to HIV-negative women. It would be better if professionals routinely assess postpartum women for sleep quality and focus on HIV-positive women.